PERAN PRAKTIK INDUSTRI, DUKUNGAN ORANG TUA, KEAKTIFAN ORGANISASI, DAN SOFT SKILL DALAM MENUNJANG KESIAPAN MEMASUKI DUNIA KERJA SISWA KELAS XI SMK DHARMA WANITA GRESIK - Riris Dwi Sulistyaningsih (Jurnal Manajerial, 2019)
This research aims to know the influence industry practices, support parents, the liveliness of the Organization and the soft skills against job readiness class XI student SMK Dharma Wanita in Gresik. The population in this research as much as 63 students of Class XI completed the industrial practice and drove a sample in this research as much as 55 students. The data type used is primary data. Testing is done using multiple linear regression analysis technique. The results of this study indicate that a variable effect on the readiness of the Industry Practice of working with t t > count table (5.656 > 2.007). Support Parents have no effect against Italy employment with t count < t table (-1.618 < 2.007). The liveliness of the Organization have no effect against Italy employment with t count < t table (0.889 < 2.007). Influence of Soft Skill to Work with Readiness t calculate > t table (4.466 > 2.007) SMK Dharma Wanita in Gresik.